ECONOMICS OF PLANTING PITS UNDER SORGHUM AND PIGEON PEA IN SEMI-ARID AREAS OF EASTERN KENYA - Rebecca Yegon; Hezron Nyarindo Isaboke; Geoffrey Christopher Mrema; Peter Mtakwa (Agricultural Socio-Economics Journal, 2020)
Rainwater harvesting (RWH) is promoted in arid and semi-arid areas for increased yields. Planting pits are RWH systems that are used for collecting rainwater and runoff. Recently, there has been increased interest in economic and environmental benefits of agricultural technologies for sustainable development. To contribute to this knowledge, economics of Chololo and Five by Nine planting pits and sorghum and pigeon pea mulch was investigated at two sites in semi-arid Eastern Kenya for four seasons. The experiments were in a randomized complete block design in three replicates. Returns of planting pits and mulch were calculated by evaluating the benefit-cost (B: C) ratios and net present values (NPV) while considering water as an economic good. Planting pits were profitable for sorghum and unprofitable for pigeon pea production. The outcome differed with sites and seasons depending on rainfall availability. Chololo pits earned US$ 92 to US$ 786 per hectare whereas Five by Nine pits earned US $ 59 to US$ 955 per hectare. Mulches were beneficial for sorghum and pigeon pea production at Nkarini and unprofitable at Machang’a with the yield differing with seasons depending on rainfall availability. This study recommends Five by Nine and Chololo pits for sorghum production at Nkarini where it was economically viable in three out of four seasons.